Epidemiology of Parkinson's disease - Elbaz, A.; Carcaillon, L.; Kab, S.; Moisan, F. (Revue neurologique, 2016)
Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's. PD is considered a multifactorial disorder that results, in most cases, from the combined effects of multiple risk and protective factors, including genetic and environmental ones. This review discusses some of the methodological challenges involved in assessing the descriptive, prognostic and etiological epidemiological studies of PD, and summarizes their main findings.